The Importance Of Speaking Skills For EFL Learners - Sherbekova, Sevinchbonu (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
The article studies the role of speaking skills in learning a foreign language, as it enables learners to express their thoughts, ideas, and emotions effectively for EFL (English as a Foreign Language) learners, developing speaking competence is often more challenging due to limited exposure to real communication and lack of confidence. This paper discusses the importance of speaking skills in English language learning and examines how effective teaching methods, classroom interaction, and communicative activities can enhance students’ oral proficiency.